Talkshow Ramadhan: “Ramadhan Big Sale” bagi siswa SMK Al-Fath Cibeber dan SMA Negeri 1 Cibeber - Suparman, Yogi; Hadi, Lalu Nuzul Ilham; Rizq, Abdul Malik; Assidiqi, Arif; Almubarok, Ayyub; Wardoyo, Muhammad Roki’ Fathurrohman; Ichsan, Raihan Nur (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2023)
The month of Ramadan is a very noble month with various special privilege. This privilege can only be achieved by those who are serious about bringing it to life through worship and good deeds. Therefore, community service in the form of talk shows around the month of Ramadan is very important for the community. The purpose of this community service event is to increase the spirit of worship of the students of SMK Al-Fath Cibeber and SMA Negeri 1 Cibeber in the holy month of Ramadan. The method for implementing this service is by opening a discussion forum or conversation about the month of Ramadan led by a moderator. The results of this community service are: First, this service activity ran smoothly. Second, the material presented by the speaker can be understood well by the audience. Third, this service activity ran without problems and received a positive response from the community and gave a good impression.